Achieving Optimal Treatment Targets and Minimal Disease Activity with Upadacitinib for Moderate-to-Severe Atopic Dermatitis: Integrated Analysis of Phase 3 Studies (Measure Up 1 and 2) - Jonathan I. Silverberg; Melinda Gooderham; Norito Katoh; Valeria Aoki; Andrew E. Pink; Yousef Binamer; Brad Glick; Petra Staubach; Brian Calimlim; Chao Li; Ayman Grada; Alvaro Moreira; et al. (Dermatology and Therapy)
Abstract Introduction The Aiming High in Eczema/Atopic Dermatitis (AHEAD) guidelines recommend achieving minimal disease activity (MDA) in atopic dermatitis (AD), defined as simultaneous achievement of optimal treatment targets for at least one clinician- and one patient-reported outcome (ClinRO + PRO). We assessed the effect of upadacitinib on achieving optimal ClinROs, optimal PROs, and MDA in Measure Up 1 (NCT03569293) and Measure Up 2 (NCT3607422) studies for patients with moderate to severe AD. Methods Patients were randomized to receive upadacitinib (15 mg or 30 mg) or placebo. Achievement of ≥ 1 optimal target in ClinROs, ≥ 1 optimal target in PROs, and MDA (≥ 1 optimal ClinROs and ≥ 1 optimal PROs) were reported at weeks 16 (upadacitinib vs placebo) and 52 (upadacitinib only). MDAs in selected combinations were also assessed at weeks 16 and 52. A total of 1683 and 1124 patients were included in the week 16 and 52 analysis, respectively. Results At week 16, a significantly higher proportion of patients receiving upadacitinib (15 mg: 42.5%, 30 mg: 55.9%) compared with placebo (6.4%) achieved MDA. At week 52, 57.4% and 69.9% of patients receiving 15 mg and 30 mg of upadacitinib achieved MDA, respectively. Specifically, patients receiving upadacitinib attained higher rates of ≥ 90% reduction from baseline in Eczema Area and Severity Index (EASI 90) + Worst Pruritus-Numerical Rating Scale (WP-NRS) 0/1 at week 16 (15 mg: 25.3%, 30 mg: 39.4% vs placebo: 1.8%) and maintained at week 52 (15 mg: 38.1%, 30 mg: 46.9%). Conclusion Treatment with upadacitinib achieved both ClinRO and PRO optimal treatment targets as well as MDA and may optimize overall disease management in patients with moderate-to-severe AD.